Soft-Tissue Conditions Around Dental Implants: A Literature Review. Issue 2 (April 2019) - Lin, Guo-Hao; Madi, Iman M.
Abstract : Background: The aim of this article is to review the current understanding regarding periimplant soft-tissue conditions to minimize risk of periimplant mucositis and periimplantitis. Materials and Methods: An electronic search was performed in 4 different databases. Articles were reviewed and summarized if the following criteria were met: published evidence with recommendations on soft-tissue conditions around dental implants. Results: An evaluation of various soft-tissue parameters, including the need of keratinized mucosa, periimplant mucosal height and phenotype, midfacial tissue level, and papillary fill, was performed based on the currently available evidence. Comments: The need of keratinized mucosa is the parameter investigated the most. A trend favors a need of a wide band of nonmobile keratinized mucosa is seen with the benefit of less incidence of periimplant mucositis. In addition, the influence of the mucosal height and tissue phenotype on periimplant tissue health remains inconclusive. Although other soft-tissue parameters, including papillary fill and midfacial tissue level, are not yet proven to be related to periimplantitis, they play a crucial role to achieve successful esthetics. Conclusion: A limited amount of evidence was identified to correlate periimplant soft-tissue parameters with periimplantitis. However, a wide band of nonmobile keratinized mucosa, an adequate periimplant mucosal height, and a thick tissue phenotype might reduce the incidence of tissue inflammation and future complications.